ON A CONTROL DESIGN TO AN AFM MICROCANTILEVER BEAM, OPERATING IN A TAPPING-MODE, WITH IRREGULAR BEHAVIOR - Rodrigues, Kleber dos Santos [UNESP]; Balthazar, Jose Manoel; Tusset, Angelo Marcelo; Pontes Junior, Bento Rodrigues [UNESP]; ASME (Amer Soc Mechanical Engineers, 2012)
In last decades, control of nonlinear dynamic systems became an important and interesting problem studied by many authors, what results the appearance of lots of works about this subject in the scientific literature. In this paper, an Atomic Force Microscope micro cantilever operating in tapping mode was modeled, and its behavior was studied using bifurcation diagrams, phase portraits, time history, Poincare maps and Lyapunov exponents. Chaos was detected in an interval of time; those phenomena undermine the achievement of accurate images by the sample surface. In the mathematical model, periodic and chaotic motion was obtained by changing parameters. To control the chaotic behavior of the system were implemented two control techniques. The SDRE control (State Dependent Riccati Equation) and Time-delayed feedback control. Simulation results show the feasibility of the both methods, for chaos control of an AFM system.